2010
DOI: 10.1371/journal.pone.0009794
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Trophoblast and Extraembryonic Endoderm Cell Lineages Derived from Rat Preimplantation Embryos

Abstract: BackgroundPrevious attempts to isolate pluripotent cell lines from rat preimplantation embryo in mouse embryonic stem (ES) cell culture conditions (serum and LIF) were unsuccessful, however the resulting cells exhibited the expression of such traditional pluripotency markers as SSEA-1 and alkaline phosphatase. We addressed the question, which kind of cell lineages are produced from rat preimplantation embryo under “classical” mouse ES conditions.ResultsWe characterized two cell lines (C5 and B10) which were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
0
25
1
Order By: Relevance
“…We have previously observed that the morphology of rat XEN cells varied depending on feeder versus plastic cultivation (Chuykin et al, 2010). When we cultured rat XEN cells at low density, we found that the majority of cells were rounded (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…We have previously observed that the morphology of rat XEN cells varied depending on feeder versus plastic cultivation (Chuykin et al, 2010). When we cultured rat XEN cells at low density, we found that the majority of cells were rounded (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Rat XEN cells were derived as primary cultures from preimplantation embryos of different genetic backgrounds (Debeb et al, 2009;Chuykin et al, 2010). Previous studies showed that rat XEN cells expressed Oct4 and SSEA1 (Debeb et al, 2009;Chuykin et al, 2010) and contributed efficiently to both PE and VE development after blastocyst injections (Debeb et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations